ARSITEKTUR DAN INFORMASI KINERJA: SUATU UPAYA MENINGKATKAN KUALITAS PENGANGGARAN INSTANSI PEMERINTAH (STUDI KASUS PADA BALAI DIKLAT KEUANGAN MAKASSAR) - Biswan, Ali Tafriji; Rossari, Priscilla Oktiva; Alhadi, Fajar Alhadi (Polytechnic of State Finance STAN, 2018)
ABSTRACTBudgeting is an important tool used by the management in carrying out the functions of planning and control, no exception to public sector organizations and government. The Indonesian government continues to implement the best practices of budgeting, one of which is through the implementation of performance-based budgeting.In a performance-based budgeting, the budget is prepared by formulating outputs or outcomes to be achieved. This formulation is done by the respective ministries/agencies in accordance with the functions of their respective organizations. All information related to the performance of then integrated into a document Work Plan and Budget-Ministry/Agency (RKA-K/L) as the basis of discussion of the budget document by the legislative board. However, in practice, ministries/agencies have not been able to compile performance information appropriately. The quality of outputs and outcomes compiled considered not in accordance with the strategic objectives and functions of the ministries/agencies concerned. Another problem related to budgeting is improper planning which led to the absorption of current year's budget to less than optimal. Through this paper, researchers will present problems related to the issue of the budget that comes from the weakness of the architecture and performance information on the ministries/agencies. Responding to the challenges of the need of better budgeting, the government began compiling Arsitektur dan Informasi Kinerja (ADIK) to improve the application of performance-based budgeting approach before. ADIK implementation on Financial Training Center of Makassar gives an overview effort of applying this new architecture. It is expected the new budgeting architecture implemented during Fiscal Year 2016 increases the optimum benefits. Keywords: budgeting, performance-based budgeting, performance information, ADIK. ABSTRAKPenganggaran merupakan alat penting bagi manajemen organisasi, tidak terkecuali organisasi sektor publik, dalam menjalankan fungsi perencanaan dan pengendalian. Instansi pemerintah terus berupaya mengelola praktik terbaik penganggaran, salah satunya adalah melalui penganggaran berbasis kinerja (PBK).Dalam PBK, anggaran disusun dengan merumuskan output atau outcome yang hendak dicapai. Perumusan ini dilakukan oleh kementerian/lembaga sesuai dengan fungsi organisasi masing-masing. Seluruh informasi kinerja diintegrasikan menjadi sebuah dokumen Rencana Kerja dan Anggaran Kementerian Negara/Lembaga (RKA- K/L) sebagai dokumen dasar pembahasan anggaran dengan badan legislatif. Namun pada praktiknya, kementerian/lembaga belum mampu menyusun informasi kinerja dengan tepat. Kualitas output dan outcome yang disusun belum sepenuhnya sesuai dengan sasaran strategis dan fungsi kementerian/lembaga yang bersangkutan. Masalah itu terkait erat dengan perencanaan yang kurang baik sehingga penyerapan anggaran kurang tepat sasaran.Melalui tulisan ini, dipaparkan isu permasalahan terkait anggaran yang bersumber dari lemahnya bangunan informasi kinerja pada kementerian/lembaga. Menjawab tantangan penganggaran yang lebih baik, pemerintah mulai menyusun Arsitektur dan Informasi Kinerja (ADIK) untuk mempertajam penerapan PBK. Penerapan ADIK pada Balai Diklat Keuangan Makassar memberikan gambaran upaya penerapan arsitektur yang baru ini. Diharapkan arsitektur penganggaran baru yang diimplementasikan mulai Tahun Anggaran 2016 ini meningkatkan manfaat penganggaran yang lebih optimal. Kata kunci: anggaran, PBK, informasi kinerja, ADIK.